2007
DOI: 10.3168/jds.s0022-0302(07)71603-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monopropylene Glycol on Luteinizing Hormone, Metabolites, and Postpartum Anovulatory Intervals in Primiparous Dairy Cows

Abstract: This study examined the effect of monopropylene glycol (MPG) supplementation on LH secretion, postpartum interval to first ovulation, and milk production in heifers calving with poor body condition score (BCS). Forty-seven heifers were allocated to 3 treatments: 1) heifers with high BCS (BCH; n = 13) that calved at a BCS of 3.4 (BCS scale of 1 to 5); 2) heifers with low BCS (BCL; n = 17) that calved at a BCS of 2.8; and 3) heifers with low BCS that calved at a BCS of 2.8 and were assigned to receive MPG supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 21 publications
3
28
2
4
Order By: Relevance
“…Some previous studies showed a rise of blood glucose concentration in dairy cows given propylene glycol orally (Studer et al, 1993;Grummer et al, 1994;Miyoshi et al, 2001;Rizos et al, 2008). In contrast, others did not observe any changes in blood glucose concentration after propylene glycol administration (Chagas et al, 2007;Moallem et al, 2007). In this study, the analysis of daily changes in blood glucose supports the latter studies, and that of blood glucose concentration in samples collected at 6-h intervals supports the former studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Some previous studies showed a rise of blood glucose concentration in dairy cows given propylene glycol orally (Studer et al, 1993;Grummer et al, 1994;Miyoshi et al, 2001;Rizos et al, 2008). In contrast, others did not observe any changes in blood glucose concentration after propylene glycol administration (Chagas et al, 2007;Moallem et al, 2007). In this study, the analysis of daily changes in blood glucose supports the latter studies, and that of blood glucose concentration in samples collected at 6-h intervals supports the former studies.…”
Section: Discussionsupporting
confidence: 87%
“…Under such metabolic conditions induced by administration of oral propylene glycol drenching that was adapted for ketosis therapy, no significant effect on ovarian function such as follicular growth and the development of corpus luteum was observed after the treatment. Previous study reported that long-term treatment with propylene glycol promoted the onset of first post-partum ovulation in dairy cows (Miyoshi et al, 2001;Chagas et al, 2007). In contrast, the present results appear to support another observation in dairy cows that post-partum ovarian dynamics and the first ovulation were not influenced by the treatment of propylene glycol (Rizos et al, 2008).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, higher IGF-1 and insulin during the peripartum period relate to postpartum ovarian activity. Propylene glycol has been assessed to decrease the delay of the first postpartum ovulation [59,60]; however, certain studies showed that propylene glycol treatment did not influence follicular dynamics and days to first ovulation [61] or ovulation during the first follicular wave postpartum [62]. Therefore, induction of an earlier first ovulation after parturition by improving energy status is problematic; hence, further studies are necessary to establish feeding management leading to higher IGF-1 and insulin during the peripartum period followed by the resumption of postpartum ovarian function in dairy cows.…”
mentioning
confidence: 99%
“…Gluconeogenic feed additives Propylene glycol (PGL) [13] Despite evidence of improved metabolic status, PGL failed to increase LH pulse frequency, and failed to increase the proportion of first postpartum follicle waves resulting in ovulation [14] Reduced interval from calving to first ovulation was observed and pulsatile release of LH at 2 and 5 weeks was greater in cows fed PGL [15] Cows fed PGL commenced ovarian cyclicity earlier than controls [16] Improved conception rate (33 to 57%) and day of first ovulation from 44. Soybean oil refining by-products (SORB) [24] Loss of body condition was less and first ovulation was experienced earlier in cows fed SORB Saturated fatty acid (FA), Ca-salts of t-octadecanoic FA, Ca-salts of safflower oil FA [25] Mean concentrations of glucose, IGF-1 and P4 were higher in cows fed a safflower oil enriched diet Ca salts of palm oil, Ca salts of safflower oil (SO) and fish oil (FO) [26] Overall pregnancy rate per AI was higher in cows fed an SO diet and pregnancy loss was reduced in FO-fed cows glucose and insulin and decreased plasma NEFA concentration.…”
Section: Nutritional Factor Product References Commentmentioning
confidence: 99%